Visual Pollution in Al-Abla and Al-Hadi Districts in Basra Province for the Period 2024-2025 - Ali Marzouq Al-Mousawi , Assist. Lect . Elaf (Basra studies journal, 2026)
The research aims to highlight the violations that distort the visual and aesthetic landscape in Al-Abla and Al-Hadi neighborhoods in the city of Basra, and to diagnose their psychological and environmental causes. This study analyzes the manifestations of visual pollution in Al-Abla and Al-Hadi neighborhoods of Basra during the period (2024-2025) and identifies its effects. The study relied on fieldwork to cover the problem of visual pollution, which included distributing a questionnaire to a random sample of residents (about 125 form) of the study area. Visual pollution was also documented through various photographs taken of the area during this period. The study focused on three main aspects of visual pollution: urban planning, streetscapes, and environmental appearance. These aspects were assessed using several indicators, with public taste serving as the primary criterion. The study concluded that the problem is widespread, with visual pollution present in almost every location. Therefore, this study represents a cornerstone for addressing the problem of visual pollution in the Al-Abla and Al-Hadi neighborhoods of Basra.